2008
DOI: 10.1007/s00464-008-0205-5
|View full text |Cite
|
Sign up to set email alerts
|

Mesh complications after prosthetic reinforcement of hiatal closure: a 28-case series

Abstract: Complications related to synthetic mesh placement at the esophageal hiatus are more common than previously reported. Multicenter prospective studies are needed to determine the best method and type of mesh for implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
204
1
28

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(239 citation statements)
references
References 35 publications
0
204
1
28
Order By: Relevance
“…16 There is also concern with the rare but problematic complication of mesh erosion and high risk of resection when refashioning in the presence of previous mesh. 29 Short oesophagus was probably rare in this study owing to the lack of stricture cases and nearly 30 years of availability of potent acid suppression, largely eliminating the short oesophagus. The Collis operations were done in a trial situation and did not reflect inability to reduce the cardio-oesophageal junction into the abdomen so no 'real' cases were found in the 455 procedures.…”
Section: Discussionmentioning
confidence: 80%
“…16 There is also concern with the rare but problematic complication of mesh erosion and high risk of resection when refashioning in the presence of previous mesh. 29 Short oesophagus was probably rare in this study owing to the lack of stricture cases and nearly 30 years of availability of potent acid suppression, largely eliminating the short oesophagus. The Collis operations were done in a trial situation and did not reflect inability to reduce the cardio-oesophageal junction into the abdomen so no 'real' cases were found in the 455 procedures.…”
Section: Discussionmentioning
confidence: 80%
“…This is also demonstrated by Novitsky and Rosen [1] reporting on all the different types of biological meshes and their different properties. Meshes working differently in different positions have also been illustrated by Stadlhuber et al [3] who reported of several cases of esophageal stenosis/erosion from the use of both synthetic and biological meshes for the reinforcement of the crural closure during hiatal hernia repair. In this issue of Hernia, however, Powell et al [4] illustrate that another group of meshes, namely the ''synthetic remodeling meshes'' seem to work without complications in the early phase in 70 patients who underwent hiatal repair.…”
Section: The Concept Of Biologic Meshesmentioning
confidence: 93%
“…(33) Proponents of the mesh cite lower hernia recurrence rates, while opponents cite the occurrence of complications such as dysphagia, oesophageal stenosis and erosion of the mesh into the oesophagus. (34,35) In the present study, the dissected hernia sac was routinely used as an interposition between the mesh and oesophagus to reduce the risk of erosion; there were no cases of recurrence, mesh erosion or dysphagia among the patients who received mesh implants.…”
Section: Discussionmentioning
confidence: 80%